1994
DOI: 10.1037/0012-1649.30.6.847
|View full text |Cite
|
Sign up to set email alerts
|

Imagining the outcome of pretend transformations: Assessing the competence of normal children and children with autism.

Abstract: Children's grasp of make-believe transformations was studied. In Experiment 1, children saw an adult enact a pretend change (e.g., sprinkling pretend talcum powder over a toy cat). They indicated the pretend outcome by choosing between a picture depicting no change (e.g., cat without talcum powder on its body) and a picture depicting the pretend change (e.g., cat covered with talcum powder). Older children (M = 29 months) chose correctly, but younger children (M = 21 months) did not. A similar age change emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
0
9

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 20 publications
6
33
0
9
Order By: Relevance
“…This is consistent with findings reported by Rutherford et al (2007) but inconsistent with earlier reports of intact comprehension (Jarrold et al, 1994b;Kavanaugh & Harris, 1994). However, in both of these earlier studies the children watched the experimenter pour an imaginary substance (e.g.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…This is consistent with findings reported by Rutherford et al (2007) but inconsistent with earlier reports of intact comprehension (Jarrold et al, 1994b;Kavanaugh & Harris, 1994). However, in both of these earlier studies the children watched the experimenter pour an imaginary substance (e.g.…”
Section: Discussionsupporting
confidence: 62%
“…Additionally, children with autism were found to have no difficulty comprehending the pretend play of another person (Jarrold et al, 1994b;Kavanaugh & Harris, 1994). These findings seriously challenged the impaired mentalising explanation of lack of pretense, which entails a competence deficit.…”
Section: A Problem Of Inhibition?mentioning
confidence: 96%
“…The results showed that children with autism performed as well as the controls. Robert D. Kavanaugh and Paul L. Harris [1994] conducted a similar experiment, in which an experimenter enacted the pretend transformations such as pretending to pour tea over a target toy animal or over a toy truck. Children with autism were asked to point to the picture which shows the consequence of these pretend transformations.…”
Section: A More General Solution: Rejecting Premisementioning
confidence: 98%
“…In this respect the Goodenough Draw-A-Man Test (Goodenough 1926, Harris, 1963, originally considered as a measure of intellectual ability, has also been the subject of extensive research (Kavanaugh & Harris, 1994 ). The draw a man or woman test requires children of different ages to draw a picture of a man, a woman, or themselves.…”
Section: Introductionmentioning
confidence: 99%